Effects of Resveratrol Against Induced Metabolic Syndrome in Rats: Role of Oxidative Stress, Inflammation, and Insulin Resistance. (11th August 2022) - Reda, Doha; Elshopakey, Gehad E.; Mahgoub, Hebatallah A.; Risha, Engy F.; Khan, Anmar A.; Rajab, Bodour S.; El-Boshy, Mohamed E.; Abdelhamid, Fatma M.
Abstract : Metabolic syndrome (MS) is a serious health problem associated with an increase in risk factors for hepatic steatosis, which is the most common liver disease today. The goal of this study was to investigate the protective effects of resveratrol against metabolic alterations associated with a high-fat high-fructose diet (HFFD). Thirty-two male rats were randomly divided into four equal groups: control (cont.), metabolic syndrome (MS), resveratrol (Res), and metabolic syndrome treated with resveratrol (MS + Res). Resveratrol was administrated orally at a dose of 30 mg/kg·bw, daily. After 10 weeks, body weight, serum biochemical parameters, hepatic oxidative stress, inflammatory markers, as well as mRNA levels of hepatic genes related to lipid metabolism and insulin signaling were measured. In addition, the liver was examined histopathologically to detect lipid deposition. Increased body weight, hepatic dysfunction, dyslipidemia, hepatic insulin resistance, hepatic oxidative and inflammatory stress conditions, upregulation of mRNA expression level of sterol regulatory element binding protein 1-c (SREBP1-c), and downregulation of mRNA expression levels of peroxisome proliferated activated receptor alpha (PPAR α ) and insulin receptor substrate-2 (IR-S2) were all observed in the MS rats. Hepatic steatosis was confirmed by hematoxylin and eosin and Oil Red O staining. Administration of resveratrol reduced liver steatosis, oxidative stress, and inflammatory state. Also, it improved lipid profile as well as insulin sensitivity and reverted alterations in hepatic mRNA expression levels of the tested genes. Based on these findings, resveratrol could be proposed as a therapeutic approach for MS prevention.